2017
DOI: 10.1111/xen.12321
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in Tibetan macaques following α‐1,3‐galactosyltransferase‐knockout pig liver xenotransplantation

Abstract: Here, we established a modified auxiliary liver xenotransplantation model resulting in near-normal hepatic function. Inflammatory cytokines might contribute to early damage in liver xenografts. Controlling the systemic inflammatory response of recipients might prevent early post-Tx graft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…IL‐6 is upregulated in both donor xenograft and recipients in xenotransplantation . IL‐6 was induced in adult porcine islets treated with poly I:C or LPS in vitro, administration of LPS also induced IL‐6 expression in pig‐to‐mouse islet xenotransplantation .…”
Section: Potential Pathological Role Of Il‐6 In Xenotransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐6 is upregulated in both donor xenograft and recipients in xenotransplantation . IL‐6 was induced in adult porcine islets treated with poly I:C or LPS in vitro, administration of LPS also induced IL‐6 expression in pig‐to‐mouse islet xenotransplantation .…”
Section: Potential Pathological Role Of Il‐6 In Xenotransplantationmentioning
confidence: 99%
“…Interestingly, in a pig‐to‐baboon model, induced IL‐6 was not significantly less after the transplantation of cardiac grafts from pigs with multiple genetic modifications (eg, GTKO, hCD46, hEPCR, hDAF in addition to either hTFPI and hCD47 [n = 2] or hTBM and hCD39 [n = 1]) when compared to pigs with only three genetic manipulations (GTKO, hCD46, and hTBM) (Table ) . Moreover, Zhang et al reported that the production of IL‐6 increased dramatically 1 hour after pig‐to‐monkey liver xenotransplantation with immunosuppressive therapy, but the level of IL‐6 gradually fell from day 1 to day 10 (Table ). However, the transplantation of porcine islets transduced with human HO‐1, sTNF‐αR‐Fc (soluble TNF‐α receptor type I with human IgG1 Fc), or sTNF‐αR‐Fc/HO‐1 was associated with a decrease in the level of IL‐6 compared to a control group (Table ) …”
Section: Potential Pathological Role Of Il‐6 In Xenotransplantationmentioning
confidence: 99%
“…Leukocyte, erythrocyte, and platelet sequestration can occur either during ex vivo perfusion or after in vivo transplantation, associated with adhesion and capture mechanisms, and these could be exacerbated by increased cytokine production, cell desialylation, and interspecies incompatibilities . Kupffer cells in the pig liver and circulating macrophages release proinflammatory and procoagulant factors that augment graft injury .…”
Section: Xenogeneic Liver Graft Injurymentioning
confidence: 99%
“…8,9 In particular, profound platelet loss results in lethal hemorrhage. 10,11 We here provide a systematic review of the present status of pig liver xenotransplantation and summarize relevant molecular mechanisms related to xenogeneic immunity, coagulation dysregulation, and thrombocytopenia. Our purpose is to consider strategies to overcome the current barriers to further advance pig liver transplantation toward the clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation